Sifat Dan Morfologi Bioplastik Berbasis Pati Sagu Dengan Penambahan Filler Clay Dan Plasticizer Gliserol - Anugerah Rifaldi; Irdoni Hs; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Bioplastic is one of alternative to relpace comercial plastic that can be harmful to environment. Bioplastic is made to make degradation become easier. One of potential raw material is sago because it has a highest starch component. The aims of this research are the study of impact clay as filler and glycerol as plasticizer to mechanical properties (tensile strenght, elongation, modulus young), hidrophobicity (water uptake), biodegradation and morphology. The synthesis method is solution intercalation of starch, water, filler and plasticizer with variation of filler are 3 (%w/w), 6 (%w/w), 9 (%w/w), 12 (%w/w) and glycerol are 10 (%w/w), 14 (%w/w), 18 (%w/w), 22 (%w/w). The analysis show that filler clay and glycerol give an impact to mechanical properties of bioplastic. the best mechanical properties is on bioplastic with composition 3 % filler and 14 % glycerol with tensile strenght 2.891 Mpa, % elongation 30.99 %, modulus young 9.39 Mpa. The highest hidrophobicity of bioplastic is 85.71% and residual persentation is between 67.39 % to 81.25 % in 8 day. Micrograf analysis shows that filler distribution is not be spread evenly on sago starch matrices.Keywords : bioplastic, clay, filler, glycerol, plasticizer, sago strach